2016
DOI: 10.36366/frontiers.v27i1.372
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Intercultural Relations among University Students in Canada

Abstract: Over 304,000 international students studied in Canadian universities in 2013 (CIC, 2014). In addition to their academic success, one important feature of their stay in Canada is the quality of the intercultural relations, and the adaptations they make during their stay. The present study sought to understand the intercultural relations, acculturation and adaptation of both international students and Canadian students. Fifty-seven international (all from China) and 68 domestic students were drawn from several C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…Research has shown that international students, including Erasmus students, experience acculturation stress (Ward, Okura, Kennedy, & Kojima, ) and challenges, including language barriers, cultural differences, loneliness and academic and financial strain (Gui, Safdar, & Berry, ; Scott, Safdar, Desai Trilokekar, & El Masri, ). Adapting to a new academic and sociocultural environment depends on students' ability to successfully meet the challenges in that environment.…”
Section: Mida Modelmentioning
confidence: 99%
“…Research has shown that international students, including Erasmus students, experience acculturation stress (Ward, Okura, Kennedy, & Kojima, ) and challenges, including language barriers, cultural differences, loneliness and academic and financial strain (Gui, Safdar, & Berry, ; Scott, Safdar, Desai Trilokekar, & El Masri, ). Adapting to a new academic and sociocultural environment depends on students' ability to successfully meet the challenges in that environment.…”
Section: Mida Modelmentioning
confidence: 99%
“…Moreover, students' participation in the educational process can help them to initiate and maintain a sense of affiliation with the host students, and provide further opportunities for education can lead them to understand and cope with the cultural differences (Tiemann;2004;Zentrum für Türkeistudien;. Therefore, education is not only a tool for integration but it created a multicultural environment within educational institutions in countries like Australia, Canada, America, England and the other may pose certain conditions in the multicultural atmosphere that may promote or hinder integration of the students (Gui, Safdar, & Berry, 2016;Schachner, He, Heizmann, & Van de Vijver, 2017).…”
Section: Prospects Of Students' Integrationmentioning
confidence: 99%
“…The primary goals of Australia and Canada, the earliest supporters of multiculturalism, is to provide opportunities to the immigrants of the national language(s) learning, engage them in the society equally, and identify them with the host society (Huddleston, 2011;Gui, Safdar, & Berry, 2016;Schachner, He, Heizmann, & Van de Vijver, 2017). At the same time, people are allowed to express their cultural heritage and language according to their desires.…”
Section: Prospects Of Students' Integrationmentioning
confidence: 99%
“…In cross-cultural literature, the investigation of acculturation and its outcome, cross-cultural adaptation, has been the center of interest for many researchers (e.g., Brisset, Safdar, Lewis, & Sabatier, 2010;Gui, Safdar, & Berry, 2016). Acculturation occurs when groups of people with different cultures come into ongoing direct contact with each other that results in the cultural and psychological changes of either or both groups (Berry, 1997).…”
Section: Cross-cultural Adaptationmentioning
confidence: 99%